Design and Modeling of Parallel Two-degree-of-freedom Variable Stiffness Actuator. Issue 1 (April 2020) - Yang, Shangkui; Chen, Peng; Cao, Yongzhan; Zhu, Shuyun; Ge, Zhuang; Liu, Yuwang
Abstract: In this paper, a new 2-DOF variable stiffness actuator based on a 2-DOF spherical wrist parallel mechanism is proposed. A 2-DOF VSA based on a parallel ball wrist mechanism and a parallel arrangement of leaf spring sets is used. Control its stiffness adjustment, analysis its variable stiffness principle and actuator mechanical structure. The parallel arrangement of the leaf spring groups reduces the mass and volume of the joints, enabling simultaneous adjustment of the stiffness. The analytical formula of the rotational stiffness of the actuator is established according to the geometric nonlinearity of the large deflection of the leaf spring.